2023
DOI: 10.24857/rgsa.v17n7-026
|View full text |Cite
|
Sign up to set email alerts
|

Model of Institutional Strengthening Based on Management Function and Sharia Compliance: Exploration of Islamic Cooperative Institutions in Jember Regency, Indonesia

Novi Puspitasari,
Dewi Prihatini,
Ana Mufidah
et al.

Abstract: Purpose: Sharia cooperative practices in Jember Regency, Indonesia generally do not perform well. This study explores the Islamic Cooperative Institution (ICI) practices based on management functions, the role of stakeholders, and sharia compliance at ICI in the Jember Regency.   Method: This research uses a qualitative method with a case study approach. Data mining using in-depth interviews with seven informants managing the ICI  who are still active and an informant from the Cooperatives and MSMEs Office in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Multiple studies have indicated that Islamic finance practices can enhance financial access and bolster the growth of MSMEs (Mawardi et al, 2018;A. Z. Anwar et al, 2019;Qoyum & Fauziyyah, 2019;Nurasyiah et al, 2022; M. K. Anwar et al, 2023;Puspitasari et al, 2023;Mujiatun et al, 2023). However, research on the nexus between Islamic finance practices and the MSMEs' growth in Indonesia remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have indicated that Islamic finance practices can enhance financial access and bolster the growth of MSMEs (Mawardi et al, 2018;A. Z. Anwar et al, 2019;Qoyum & Fauziyyah, 2019;Nurasyiah et al, 2022; M. K. Anwar et al, 2023;Puspitasari et al, 2023;Mujiatun et al, 2023). However, research on the nexus between Islamic finance practices and the MSMEs' growth in Indonesia remains limited.…”
Section: Introductionmentioning
confidence: 99%